DIALOGIC FEEDBACK TO PROMOTE DEEP LEARNING FOR EFL SPEAKING LEARNERS IN ONLINE LEARNING ENVIRONMENT: STUDENTS’VOICES - Arinda, Putri; Sadikin, Irma Savitri (PROJECT (Professional Journal of English Education), 2021)
English as a foreign language (EFL) students, regardless of their ability to speaking English, encounter significant speaking challenges. They lack motivation and confidence to speak English in online learning environment, which is particularly during a global pandemic. Therefore, the present study aims to analyse the implementation of dialogic feedback in online learning for the students speaking skills and investigate the students’responses to the implementation of dialogic feedback in teaching speaking. The respondents of this study were tenth-grade students attending a private senior high school in Bangka Belitung. This study employed a qualitative approach with a case study design. Interviews and observation were employed as instruments. The findings of this study indicated that the majority of students were engaged in online speaking classes toward implementing dialogic feedback; they were able to clarify their confusions from the teacher's feedback during presentations and they were able to improve their errors in some aspects of speaking skills, such as pronunciation and intonation when telling a story.  Most students in an online class showed positive attitude toward dialogic feedback. They revealed that dialogic feedback is necessary for learners to improve their speaking abilities and enabled them to gain new knowledge through communication and sharing of new vocabulary. However, a few of the students stated technical issues and poor internet connection on the internet could be impediments during the class session.Keywords: Dialogic feedback, speaking skills, students’ perception.